School Competitions as Catalysts for Learning Resource Center Development and Academic Culture in Elementary Schools: A Systematic Review - Sukaesih, Sukaesih; Saud, Udin; Hendriawan, Deri (Journal of Innovation and Research in Primary Education, 2025)
School competitions have the potential to enhance motivation and achievement among primary school students; however, the mechanisms through which competitions catalyze the transformation of Learning Resource Centres (PSB) to strengthen long-term academic culture remain underexplored. The limited literature integrating these three domains necessitates a systematic synthesis. Purpose: To examine systematically how school competitions function as catalysts for PSB revitalization and their influence on academic culture in elementary schools. Method: A Systematic Literature Review (SLR) was conducted using the PRISMA framework, analyzing 50 articles (2018–2024) retrieved from Scopus, ERIC, Google Scholar, Semantic Scholar, and PubMed. The inclusion criteria comprised empirical or conceptual studies that addressed elementary school competitions, PSB roles, and academic culture. Thematic analysis was applied to identify patterns of catalytic effects, integration models, and impacts on academic culture. Principal Results: The review revealed that school competitions frequently stimulate improvements in PSB collections, enhance teacher capacity through targeted training, and increase student engagement with PSB resources. These catalytic processes collectively support the development of a sustainable academic culture in elementary schools. Major Conclusions: Well-designed school competitions can transform PSBs from passive repositories into dynamic learning environments, fostering an enduring culture of academic engagement. Effective implementation requires supportive policies, adequate funding, and integration into daily learning practices. The study extends Activity Theory by illustrating the mechanisms through which competitions act upon the PSB ecosystem and offers a model for policymakers to bridge infrastructure gaps while strengthening academic culture organically.